Galileo and the Enigma of -ic/-ical Adjectives: New Techniques to Meet Old Challenges - Lidong, Ma; Tarp, Sven (HERMES - Journal of Language and Communication in Business, 2020)
One of the challenges that non-native speakers are facing when writing in English is the use of the suffixes -ic and -ical in connection with a big number of adjectives. L2 learners, even at a high proficiency level, sometimes have doubts about the form they should use in a concrete context. Other times they are simply not aware that they have a problem. The article will look at the assistance they can get in traditional dictionaries as well as some of the new digital writing assistants. It will analyze and classify adjectives ending in -ic and -ical and try to detect some trends that may be relevant for learners at different levels. It will then propose a multidimensional solution that can be incorporated into a digital writing assistant. The proposal includes various types of assistance, even to writers who are not aware of any problem. It also has a pedagogical dimension that makes it particularly relevant to non-native learners of English.